The Economics of Exclusion: Trumpism, Identity Politics, and the Future of Fiscal Policy - Abdelaziz Abdalla Alowais (Journal of Informatics Education and Research, 2025)
This study examines the impact of Trumpism in reconfiguring U.S. fiscal policy towards the purpose of identity-based exclusion through notable strategies such as tax reforms and welfare constraints, as well as budgetary redlining of cultural majorities. Combining fiscal sociology, symbolic interactionism, and critical race theory, the study utilized qualitative case studies of legislative language, public rhetoric, and policy discussions to dissect the latent inequities. The study findings reveal that policies, including the 2017 Tax Cuts and Jobs Act, primarily benefited wealthy white communities. Such moves sustain the narrative of “deservingness,” increasing the economic as well as racial disparities. The study demands a change in emphasis to economic justice by advocating for universal and race-neutral taxation policies and intersectional rights that deal in depth with issues of intersecting race, class, and citizenship. By highlighting the long-term effects, the research advances the need for prolonged longitudinal studies to assess long-term socioeconomic consequences. The study significantly contributes to the existing literature and also provides practical policy recommendations integrated into the study to support conversations on how to attain equitable governance in the era of populist fiscal nationalism.